2010
DOI: 10.1891/0886-6708.25.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Intimate Partner Violence and Associated Risk Factors Among Married Enlisted Female Soldiers

Abstract: A sample of 248 enlisted active duty females married to civilian spouses completed a self-report survey that asked about their own and their spouse's violence. The survey also asked about their sex-role attitudes, marital satisfaction, alcohol use, childhood trauma, and depression. Results identifi ed patterns of intimate partner violence and their relationship to the psychosocial risk factors. Females experiencing severe bidirectional violence were likely to be the most depressed and to have a history of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 61 publications
(64 reference statements)
3
39
1
Order By: Relevance
“…One recent systematic review of data from the East Asia and Pacific Region reported that children who had been sexually abused had a threefold increase in risk of IPV victimization later in life (Fry, McCoy, & Swales, 2012). In studies of civilian women (Caetano, Ramisetty-Mikler, & Field, 2005) and female enlisted soldiers married to civilian men (Forgey & Badger, 2010), women reporting severe bi-directional IPV were more likely to endorse a child sexual abuse history. In a large nationally representative Canadian sample, childhood sexual abuse was associated with later IPV victimization for women and men, although the relationship was stronger for women than for men (Daigneault, Hebert, & McDuff, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One recent systematic review of data from the East Asia and Pacific Region reported that children who had been sexually abused had a threefold increase in risk of IPV victimization later in life (Fry, McCoy, & Swales, 2012). In studies of civilian women (Caetano, Ramisetty-Mikler, & Field, 2005) and female enlisted soldiers married to civilian men (Forgey & Badger, 2010), women reporting severe bi-directional IPV were more likely to endorse a child sexual abuse history. In a large nationally representative Canadian sample, childhood sexual abuse was associated with later IPV victimization for women and men, although the relationship was stronger for women than for men (Daigneault, Hebert, & McDuff, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They include witnessing and experiencing abuse in childhood, previous violence victimization and perpetration, social deprivation and substance misuse [14]. Occupationspecific risk factors have also been identified [15][16][17][18], with evidence suggesting length of deployment as a risk factor for domestic violence perpetration [19]. Similarly, combat stress is shown to be associated with domestic violence perpetration among active-duty military personnel [20], military veterans [21] and prisoners of war [22].…”
Section: Introductionmentioning
confidence: 99%
“…Types of violence committed by women may be less severe (Taft, et al, 2009) and women’s violence often occurs in the context of violence against them by male partners (Swan et al, 2008). Although the pattern of IPV is most often bidirectional (Forgey & Badger, 2010), and spouses of male veterans with PTSD have reported greater perpetration of violence towards their spouses with PTSD (Jordan et al, 1992), evidence suggests that PTSD symptoms in women are a unique predictor of subsequent exposure to interpersonal violence victimization (Cougle, Resnick, & Kilpatrick, 2009). For this reason, it is important to examine both victimization and perpetration as it occurs in women with PTSD.…”
mentioning
confidence: 99%